A study on the relational response of comparison based on the acceptance of psychoactive substances using the IRAP - Oliveira, César Silva Rodrigues; de Almeida, João Henrique; Bortoloti, Renato; de Oliveira, Thais Porlan; Huziwara, Edson Massayuki (Perspectivas em Análise do Comportamento, 2021)
The present study aimed to evaluate, through the Implicit Relational Assessment Procedure (IRAP), the existence of a comparative relational response based on the acceptance of psychoactive substances. It was possible to argue that even people who have never consumed such substances would be able to develop an order of acceptance similar to the order of consumption of these drugs in Brazil (i.e., alcohol more acceptable than tobacco; tobacco more acceptable than marijuana; and marijuana more acceptable than cocaine). Undergraduate students with low levels of alcohol consumption and with no previous history of tobacco, marijuana, and cocaine use participated in the study. Participants completed four Likert scales to assess the acceptance of each psychoactive substance and responded to an IRAP programmed to assess the relational response of comparison between the four psychoactive substances previously mentioned. Our findings did not confirm the hypothesis that the order of acceptance of psychoactive substances would follow the order of prevalence of use of these substances. In a post hoc analysis, only the data from IRAP served to differentiate participants with and without previous experience with alcohol. Considerations are made regarding the relationship between specific attitudes about psychoactive substances and their use, as well as about the programming of stimuli in IRAP and their limitations for assessing the relational response of comparison.